2011
DOI: 10.1111/j.2042-3306.2011.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Thoroughbred and Quarter Horse racehorses that sustained a complete scapular fracture

Abstract: Despite breed differences for signalment and exercise distances, both breeds incur a complete scapular fracture that is more likely to occur in the right scapula of young and older, male racehorses, early in their race career or after few races. Quarter Horses sustain a catastrophic scapular fracture more frequently than TBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 29 publications
9
38
1
Order By: Relevance
“…However, the picture is not simple. In some investigations, as here, risk is carried disproportionally by young and by older horses, while middle‐aged animals tend to have relatively low risk . Young horses may more frequently have problems with temperament and tractability, be predisposed to injuries reflecting skeletal immaturity and be more prone to fatigue, while older horses may suffer from cumulative damage.…”
Section: Discussionmentioning
confidence: 82%
“…However, the picture is not simple. In some investigations, as here, risk is carried disproportionally by young and by older horses, while middle‐aged animals tend to have relatively low risk . Young horses may more frequently have problems with temperament and tractability, be predisposed to injuries reflecting skeletal immaturity and be more prone to fatigue, while older horses may suffer from cumulative damage.…”
Section: Discussionmentioning
confidence: 82%
“…By contrast, in the USA, Vallance et al . identified that 55% of scapular fractures occurred during training. Additionally, in the current study all scapular fractures occurred in the right forelimb.…”
Section: Discussionmentioning
confidence: 99%
“…Racehorse attrition and fatalities due to musculoskeletal injuries are high. In California, approximately one Thoroughbred racehorse dies racing or training at a racetrack due to a musculoskeletal injury for every 24 racehorses that start in a race [1]. Racetrack surface is one of several risk factors associated with racehorse injury and death, but the observed associations of different surface materials with injury risk are not consistent, probably due to confounding factors inherent in epidemiological studies [2].…”
Section: Introductionmentioning
confidence: 99%